Pepper Disease Assessment and Identification in Major Growing Districts of West Gojam Zone in Northwestern Ethiopia - Abebe, Azanaw; Abera, Merkuz (International Journal of Sustainable Agricultural Research, 2019)
Hot pepper (Capsicum annuum) is an economically and traditionally an important crop in Ethiopia. It is also necessary vegetable crop mainly for small-scale farmers in Amhara National Regional State of Ethiopia. The productivity of this crop is low under national level, it is said to be 7.36qt per hectare. It is even lower to that of the national in Amhara National Regional State growing areas. Assessing pepper growing areas and collect damaged plants by the disease and identification of diseases was the focus of this study. Three districts were selected purposively based on accessibility, production and problem, available time, logistics, and representativeness. In each district three representative peasant administrations (PAs)/kebeles were selected. Sampled kebeles and respondents were selected using simple random sampling techniques. A total of 135 respondents were selected for interview. The data was collected through semi structured interview schedule. In each PA, three simple random sample selected farmers’ fields were assessed. The assessment was done at one growth stage of the plant (flowering-podding stage). The collected data was analyzed using descriptive statistics. The findings of this study confirm that in all the surveyed peasant farms, only one type of variety, which is Marekofana was encountered with low to high levels infestation of different leaf, stem, and root diseases. Root rot/wilt complex diseases were found distributed in almost all the surveyed areas. The prevalence of the disease, pepper wilt/root rot complex is high, therefore; efforts better to be made towards the integration of multiple control options.